Prevalence of monogenic disease in paediatric patients with a predominant respiratory phenotype. Issue 2 (16th June 2021) - Dai, Dan; Mei, Mei; Hu, Liyuan; Cao, Yun; Wang, Xiaochuan; Wang, Libo; Lu, Yulan; Yang, Lin; Dong, Xinran; Wang, Huijun; Wu, Bingbing; Qian, Liling
Abstract : Objective: This study aimed to investigate the prevalence and clinical characteristics of monogenic disease in paediatric patients with a predominant respiratory phenotype. Methods: Exome sequencing was performed in a cohort of 971 children with a predominant respiratory phenotype and suspected genetic aetiology. A total of 140 positive cases were divided into subgroups based on recruitment age and the primary biological system(s) involved. Results: There were 140 (14.4%) patients with a positive molecular diagnosis, and their primary clinical manifestations were respiratory distress (12.9%, 18 of 140), respiratory failure (12.9%, 18 of 140) and recurrent/persistent lower respiratory infections (66.4%, 93 of 140). Primary immunodeficiency (49.3%), multisystem malformations/syndromes (17.9%), and genetic lung disease (16.4%) were the three most common genetic causes in the cohort, and they varied among the age subgroups. A total of 72 (51.4%) patients had changes in medical management strategies after genetic diagnosis, and the rate in those with genetic lung disease (82.6%, 19 of 23) was far higher than that in patients with genetic disease with lung involvement (45.3%, 53 of 117) (p=0.001). Conclusion: Our findings demonstrate that exome sequencing is a valuable diagnostic tool for monogenic diseases in children with a predominant respiratory phenotype, and the genetic spectrum varies with age. Taken together, genetic diagnoses provide invaluable clinical and prognostic information that may also facilitate the development of precision medicine for paediatric patients. Abstract : This manuscript reports on the prevalence and clinical characteristics of monogenic disease in paediatric patients with a predominant respiratory phenotype. And that exam sequencing is a valuable tool for this with 140 positive cases in a cohort of 971.